Christianizing the Social Order and Founding Myths: Double Vision? - Airhart, Phyllis D. (Toronto journal of theology, 1996)
Can we say that "Christianizing the social order" was the founding vision of the United Church? This question nagged me as the Lilly Project Committee made plans for what we were accustomed to calling our "founding vision" conference. As we cast about for a theme, there was some hesitation in identifying it as the founding vision. To me the phrase conjured up images of the turn-of-the-century social gospel movement and the Christian socialism which in the 1930s found expression in the report of the United Church commission by that name. There is no doubt that these were crucial episodes in the story of the United Church and its antecedents. But was it really the "founding vision?"